Designing Solar-Powered Electric Vehicle Charging Stations for the Development of Future Green Cities - Hoang Minh Vu Nguyen; Nguyen Ngoc Nhu To; Thuy Anh Tran; Hoang Trung Nguyen (Journal of Technical Education Science, 2024)
This paper presents an overview of the ideas, general design, and preliminary cost estimation for electric vehicle charging stations in planned areas. The selection of a charging station model that integrates solar panels connected to the national grid, having energy storage unit is discussed. This model is suitable for certain urban areas with potential for solar energy usage in electricity generation, contributing to efficient energy use, emission reduction, and decreased electricity consumption from the national grid, aiming towards zero-emission cities and environmental protection. The calculation process is based on the technical specifications of the Vinfast electric vehicle, with a battery capacity of 42kWh. The preliminary estimates of the research indicate that the initial investment cost is very high. However, the potential for capital recovery from the system is quite rapid and feasible upon implementation. The research calculations show that an integrated solar energy electric vehicle charging station system is feasible for the Ba Tơ town area in Quang Ngai province. The research results provide a planning orientation for technical infrastructure systems in sustainable and modern urban development in the coming years.